WYKORZYSTANIE NARRACJI BIOGRAFICZNYCH W REFLEKSJI NAD KSZTAŁCENIEM NAUCZYCIELI JĘZYKÓW OBCYCH - Wąsikiewicz-Firlej, Emilia; Lankiewicz, Hadrian (Neofilolog, 2019)
This paper attempts to contribute to the discussion on the use of biographical narratives in investigating FL teacher careers and bring to light their potential in teacher education, especially in the process of developing teacher identity and reflexivity. Biographical narratives provide indepth insights into individual professional careers which are viewed holistically, in the context the narrator’s life. Focused on the subjective dimensions of professional careers, narratives involve identification and interpretation of key events and persons in particular life stories, which stimulate the narrator’s reflexivity and enable them to find connections between episodes and make them meaningful.